Gladys Black letter to Nicholas S. Halmi regarding sightings of Snowy Owls and a Goshawk, February 25, 1977 - Black, Gladyset al (1977)
Sightings of Snowy Owls in Guthrie County, Poweshiek County, and Lake Red Rock and a Goshawk in Fayette County contributed by Gladys Black in a letter to Nicholas S. Halmi. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1976-1977. Epson - sheet feed/flatbed